Predictive inferencing in adults with right hemisphere brain damage. - Lehman-Blake, Margaret T.; Tompkins, Connie A. (Journal of Speech, Language & Hearing Research, 2001)
Predictive inferencing was evaluated in 13 adults with right hemisphere damage (RHD) and 11 adults without brain damage (NBD). Brief narrative stimuli that strongly suggested a single outcome were constructed to vary recency of mention of inference-related information. Reading times were recorded for narrative-final sentences that disconfirmed the target inferences. Slowed reading time on the final sentences was an indicator of inference generation. Adults with RHD generated target predictive inferences in contexts with recent mention of strongly biasing inference-related information. This group also evidenced maintenance of inferences over time, but to a lesser degree than participants in the NBD group. Overall, individuals with better auditory comprehension or larger estimated working memory capacity tended to maintain inferences better than did the other participants. The results are discussed in relation to current hypotheses of inferencing and discourse comprehension in adults with RHD. Reprinted by permission of the publisher.